2016
DOI: 10.1177/0269215516658337
|View full text |Cite
|
Sign up to set email alerts
|

Early or delayed provision of an ankle-foot orthosis in patients with acute and subacute stroke: a randomized controlled trial

Abstract: We found positive effects of providing ankle-foot orthoses in (sub)acute stroke subjects that had not used these orthoses before.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 31 publications
0
60
0
Order By: Relevance
“…We already reported positive effects of AFO provision on ankle kinematics early after stroke (17), while no effects of early vs delayed AFO provision on pelvis, hip and knee kinematics were found after 26 weeks (18). At the same time, beneficial effects of AFO provision were found on functional levels (12). After 26 weeks no differences with respect to balance and mobility were found between early and delayed provision, but early provision showed favourable outcomes in the first 11-13 weeks, possibly resulting in earlier independent and safe walking (19).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We already reported positive effects of AFO provision on ankle kinematics early after stroke (17), while no effects of early vs delayed AFO provision on pelvis, hip and knee kinematics were found after 26 weeks (18). At the same time, beneficial effects of AFO provision were found on functional levels (12). After 26 weeks no differences with respect to balance and mobility were found between early and delayed provision, but early provision showed favourable outcomes in the first 11-13 weeks, possibly resulting in earlier independent and safe walking (19).…”
Section: Discussionmentioning
confidence: 80%
“…AFO-fitting was performed by a licensed orthotist. AFO type was chosen according to a custom-developed protocol (12). Besides the AFO-intervention, all subjects received usual care from experienced physiotherapists according to the Dutch guidelines for physiotherapy after stroke (13,14).…”
Section: Provision Of Ankle-foot Orthosesmentioning
confidence: 99%
“…Momosaki et al [21] suggested that stroke survivors had better functional recovery if they were prescribed an AFO than if they were not prescribed an AFO. Nikamp et al [22] also described positive effects of providing AFO in subacute stroke patients who had not used these orthosis before from a randomized control trial. Furthermore, walking training is possible with KAFOs for patients with severe paralysis.KAFOs for hemiplegia in stroke patients have been used since the prewar time in our country [23], but orthotic therapy for gait training has only been performed in the recent 30 years [17].…”
Section: Discussionmentioning
confidence: 99%
“…A detailed description of our study design and patient inclusion can be found in our previous paper. 65 In summary, we recruited unilateral ischemic or hemorrhagic stroke subjects from the Roessingh, Centre for Rehabilitation in Enschede, the Netherlands. Subjects were maximal six weeks post-stroke and had an indication for use of an AFO.…”
Section: Methodsmentioning
confidence: 99%
“…58 We previously reported the short-term results of an explorative randomised controlled trial to study the effects of providing off-the-shelf AFOs on two different moments poststroke. 65 We included patients within six weeks post-stroke and provided them with an AFO in week 1 (early) or 9 (delayed) of the study. The effects of provision were studied after two weeks.…”
Section: Introductionmentioning
confidence: 99%